Physical health complications in children and young people with avoidant restrictive food intake disorder (ARFID): a systematic review and meta-analysis - Nadia Micali; Lee D Hudson; Simon J Russell; Rachel Marie James; Jonathan O'Shea (BMJ Publishing Group, 2024)
Background Avoidant restrictive food intake disorder (ARFID) is a feeding and eating disorder with known acute and longstanding physical health complications in children and young people (CYP) and commonly presents to paediatricians.Objective To systematically review the published literature on physical health complications in CYP with ARFID using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Methods A systematic search of PubMed, Embase, Web of Science, PsycINFO and Cochrane Library was performed on 14 February 2024. Studies reporting physical health complications in CYP ≤25 years with ARFID were included. We pooled studies for meta-analysis comparing ARFID with healthy controls or anorexia nervosa (AN).Results Of 9058 studies found in searches, we included 132 studies. We found evidence for low weight, nutritional deficiencies and low bone mineral density. CYP with ARFID can present across the weight spectrum; however, the majority of CYP with ARFID were within the healthy weight to underweight range. Most studies reported normal range heart rates and blood pressures in ARFID, but some CYP with ARFID do experience bradycardia and hypotension. CYP with ARFID had higher heart rates than AN (weighted mean difference: 12.93 bpm; 95% CI: 8.65 to 17.21; n=685); heterogeneity was high (I2: 81.33%).Conclusion There is a broad range of physical health complications associated with ARFID requiring clinical consideration. Many CYP with ARFID are not underweight yet still have complications. Less cardiovascular complications found in ARFID compared with AN may be related to chronicity.PROSPERO registration number CRD42022376866.